"They Know Me and My Situation—Patients' and Spouses' Perceptions of Person-Centered Care in Hospital-at-Home Care". Issue 6 (November 2021) - Vaartio-Rajalin, Heli; Fagerström, Lisbeth; Santamäki-Fischer, Regina
Abstract : Realization of person-centered care (PCC) is contextual. How is it perceived at hospital-at-home? Pairwise telephone interviews of patients (n = 27) and their spouses (n = 18) emerged in 4 themes. Care was found to be person-centered when both the principles and activities that underpin the concept PCC were realized.